2013
DOI: 10.1016/j.jtcvs.2012.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of conversion to thoracotomy for video-assisted thoracoscopic lobectomy: A retrospective analysis and the influence of computed tomography–based calcification assessment

Abstract: Calcification score based on the location and degree of calcifications can predict the increased likelihood of video-assisted thoracoscopic surgery conversion. This scoring system could be one element used to choose the approach for a lobectomy, especially during a surgeon's learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
2
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 11 publications
3
99
2
12
Order By: Relevance
“…Among the varied reasons for increased rates of complications, conversion to open surgery or planned conventional open surgery is the presence of difficult hilar or interlobar lymphadenopathy (6)(7)(8). This difficult to manage lymphadenopathy can be seen in the post induction setting, leading to a potentially increased risk of pulmonary arterial injury (7,9,10). While many thoracic surgeons advocate prompt conversion to thoracotomy in the setting of pulmonary arterial injury, with experience a minimally invasive approach to repair can be safe and effective.…”
Section: Textmentioning
confidence: 99%
“…Among the varied reasons for increased rates of complications, conversion to open surgery or planned conventional open surgery is the presence of difficult hilar or interlobar lymphadenopathy (6)(7)(8). This difficult to manage lymphadenopathy can be seen in the post induction setting, leading to a potentially increased risk of pulmonary arterial injury (7,9,10). While many thoracic surgeons advocate prompt conversion to thoracotomy in the setting of pulmonary arterial injury, with experience a minimally invasive approach to repair can be safe and effective.…”
Section: Textmentioning
confidence: 99%
“…However, conversion is due to prolongation of the operative time and an increase in blood loss, including emergency hemorrhage. Hanna, et al 30) classifi ed the causes of conversion into four types: intraoperative complications, technical problems, anatomical problems, and oncological conditions, and it is important to recognize these, make efforts to avoid conversion, 31) learn troubleshooting, and prepare for an emergency. 32,33) The merits of thoracoscopic surgery have been clarifi ed, and the usefulness of its active application for the elderly has been described.…”
Section: Thoracoscopic Lobectomy For Primary Lung Cancermentioning
confidence: 99%
“…Several demographic and clinical factors such as older age, history of the granulomatous disease, current COPD or smoker, and reduced forced expiratory volume in 1 second (FEV 1 ) have been identified to be predictors of intraoperative conversion (7)(8)(9). Additionally, recent studies revealed that computed tomography (CT) images with hilar lymph node calcification could predict intraoperative conversion, which was associated with adhesion of lymph nodes to hilar structures and subsequent difficulty in the dissection of hilum (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent studies revealed that computed tomography (CT) images with hilar lymph node calcification could predict intraoperative conversion, which was associated with adhesion of lymph nodes to hilar structures and subsequent difficulty in the dissection of hilum (8)(9)(10). However, even lymph nodes without calcification on CT images revealed extensive perihilar granulomatous inflammation during the operation, which required conversion to thoracotomy (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation